Epidemiology of endometriosis in Kazakhstan: a national population-based cohort analysis (2014–2019) using data from the national electronic healthcare system - Aimagambetova, Gulzhanat; Sakko, Yesbolat; Ukybassova, Talshyn; Terzic, Milan; Marat, Aizada; Kamzayeva, Nazira; Gusmanov, Arnur; Zhakhina, Gulnur; Yerdessov, Sauran; Mussina, Kamilla; Syssoyev, Dmitriy; Gaipov, Abduzhappar (Frontiers in Medicine, 2025)
BackgroundEndometriosis is a condition affecting reproductive-age women and associated with dysmenorrhea, pelvic organs dysfunction, pelvic pain, and infertility. The real epidemiology of endometriosis remains underestimated. No data are available on prevalence of endometriosis in Kazakhstan. Therefore, the aim of this was to investigate the epidemiology, complications, surgical management approach, and outcomes of endometriosis in Kazakhstan by analyzing large-scale Kazakhstani healthcare data from the Unified Nationwide Electronic Health System (UNEHS).MethodsA population-based study among women with endometriosis treated in any healthcare setting of the Republic of Kazakhstan during the period of 2014–2019 was performed. The International Classification of Diseases (ICD) 10th edition was used to retrieve data on endometriosis (“N80” and “N97”). ICD 9th edition’s procedural codes were utilized to retrieve information on surgical procedures performed to manage patients with endometriosis.ResultsIn total, 7,682 records of women diagnosed with endometriosis were analyzed from all Kazakhstani regions. The overall prevalence of endometriosis among Kazakhstani female population was 0.12%, with 50.1% of them suffering from endometriosis of the uterus, 34.5% with ovarian endometriosis, and 9.5% with endometriosis of pelvic peritoneum. The most affected group was reproductive-age women (25–44 years old). Endometriosis rates were higher among women of 35–39, 40–44, and 45–49 years old age groups – 0.4 per 1000 women of corresponding age. The most common procedures performed for surgical management were laparoscopic cystectomy and closed biopsy of the uterus, 16.4 and 13.5%, respectively.ConclusionAmong all registered cases of endometriosis, ovarian endometriosis is the most prevalent condition. However, the analysis of the UNEHS records on endometriosis reveals incomplete and inconsistent registration of the disease, which results in the underestimation of the disease’s real burden. Clinical specialist and health authorities in Kazakhstan must work to ensure the endometriosis proper diagnosis end registration to improve the disease management and outcomes.